A comparison between vibration assisted and conventional drilling of CFRP/Ti6Al4V stacks. Issue 10 (27th July 2019) - Xu, Jinyang; Li, Chao; Chen, Ming; Ren, Fei
ABSTRACT: The present paper contributes to the scientific understanding of the effects of the low-frequency vibration assisted drilling (LFVAD) process on the machinability of multilayer CFRP/Ti6Al4V stacks. The significance of the work is to analyze quantitatively how the LFVAD affects the drilling forces, cutting temperatures, hole quality attributes and drill wear extents while machining the multi-material specimens and how much improvement of hole quality and tool life can be achieved via the LFVAD when compared with the conventional twist drilling. It is found that the drilling forces and machining temperatures could be significantly reduced when using the LFVAD process for CFRP/Ti6Al4V stacks. The surface roughness of cut stack holes, exit burr heights of titanium holes as well as the composite delamination are significantly decreased via the LFVAD because of the improved titanium chip ejection. The results confirm the feasibility of the LFVAD method in improving the surface quality and tool life when drilling the multilayer stacks and indicate the applicability of the LFVAD for the future aerospace manufacturing community.